Significance of pressure solution structures analysis for fluid flow studies - examples from Struga 1 well (Zechstein Main Dolomite; W Poland) – first results - Górka, Joanna Weronika; Świerczewska, Anna; Krzyżak, Artur (Geology, Geophysics and Environment, 2015)
The abstract studies the role of pressure solution structures i.e. stylolites and solution seams for fluid flow in dolomites from the Polish part of the Zechstein Main Dolomite (Ca2).The internal structure and composition of them may influence petroleum generation and migration.